THE EFFECT OF LITERACY HABITS AND THE USE OF AL-QURAN LEARNING METHODS ON STUDENTS' AL-QURAN READING ABILITY - Arinda Rosalina; Avip Nurdarmawan; Kharisma Eka Firmanda (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
This research is based on a phenomenon seen in educational institutions at elementary, middle school, high school and even college levels, namely not being able to read the Al-Qur’an properly and correctly. This research is descriptive quantitative research with a correlation design that aims to find out how big the relationship is between literacy habits and the use of Al-Qur’an learning methods on students' ability to read the Al-Qur’an. The data analysis method is carried out using multiple linear regression analysis through the classic assumption test which consists of six tests on secondary data. The results of the research showed that the significance obtained was 0.000 so it was less than 0.05 (Sig.<0.05) so it was concluded that the implementation of Al-Qur’an literacy habits had a significant influence on the ability to read the Al-Al-Qur’an, while the significance of the variable secondly (using the Al-Qur’an learning method) it was found that the significance value was 0.325 so it was less than 0.05 (Sig.>0.05) so there was no significant influence on the ability to read the Al-Qur’an.